Effect of sintering on mechanical properties of ceria reinforced yttria stabilized zirconia. Issue 9 (July 2016) - Maurya, Rita; Gupta, Alka; Omar, Shobit; Balani, Kantesh
Abstract: Fully stabilized (8 mol%Y2 O3 ) zirconia (8YSZ) reinforced with 5, 10 and 15 wt%CeO2 are processed via spark plasma sintering (SPS) and conventional pressure less sintering (CS). Higher reduced modulus (Er, 187.5 GPa) and hardness (H, 16.2 GPa) are observed in 8YSZ processed by CS when compared to that of SPS (i.e. Er 135.3 GPa and H 9.04 GPa), which is attributed to the extent of sintering. Several factors, such as thermal conductivity, and porosity are examined as governing factors in order to quantify the extent of sintering. Thermal conductivity of a bulk sample is estimated using various models taking porosity, crystallite size etc. into consideration. Higher extent of sintering is observed for CS pellets (by ≥ 1–2 times) in comparison to that of SPS 8YSZ-CeO2 samples affirming the enhanced elastic modulus of CS pellets. Further, the smaller indent size to grain size ratio observed for CS pellets (0.01–0.03 times) contribute toward their enhanced damage tolerance during indentation when compared to that of SPS pellets ( 15–33 times). Thus, CS processing may elicit enhanced structural integrity of 8YSZ-CeO2 composites for fuel cell applications.